1996
DOI: 10.1074/jbc.271.47.29799
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Sites of Regulation of Expression of the Rat Cationic Amino Acid Transporter Gene

Abstract: Cat-1 is a protein with a dual function, a high affinity, low capacity cationic amino acid transporter of the y ؉ system and the receptor for the ecotropic retrovirus. We have suggested that Cat-1 is required in the regenerating liver for the transport of cationic amino acids and polyamines in the late G 1 phase, a process that is essential for liver cells to enter mitosis. In our earlier studies we had shown that the cat-1 gene is silent in the quiescent liver but is induced in response to hormones, insulin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
78
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 57 publications
4
78
0
Order By: Relevance
“…We previously showed that the increased Cat-1 protein expression during amino acid deprivation is due to increased mRNA levels and enhanced translation of the mRNA (6 -11). We also showed that the increased mRNA levels are mainly due to increased mRNA stability mediated by sequences within the 4.5-kb 3Ј-UTR of the 7.9-kb cat-1 mRNA (10,12). It is shown here that an 11-residue AU-rich element in the distal 217 bases of the 3Ј-UTR is required for increased mRNA stability during amino acid starvation.…”
mentioning
confidence: 71%
“…We previously showed that the increased Cat-1 protein expression during amino acid deprivation is due to increased mRNA levels and enhanced translation of the mRNA (6 -11). We also showed that the increased mRNA levels are mainly due to increased mRNA stability mediated by sequences within the 4.5-kb 3Ј-UTR of the 7.9-kb cat-1 mRNA (10,12). It is shown here that an 11-residue AU-rich element in the distal 217 bases of the 3Ј-UTR is required for increased mRNA stability during amino acid starvation.…”
mentioning
confidence: 71%
“…In brain astrocytes, lipopolysaccharide/interferon ␥ induced CAT2 but not CAT1 (20). Various signals that cause transition of cells from the resting state to the proliferating state appear to activate CAT1 expression (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of the Promoter Regulatory Region of the cat-1 Gene-Rat genomic DNA clones were isolated by PCR screening of a P1 phage genomic library using oligonucleotides from the 5Ј-end of the available cat-1 cDNA (27). We obtained three clones that cover this region with inserts of ϳ70 kb each.…”
Section: Induction Of Cat-1 Gene Expression By Amino Acid Starvation-mentioning
confidence: 99%